COVID-19 Induced Economic Uncertainty: A Comparison between the United Kingdom and the United States - Pata, Ugur Korkut (Ekonomika, 2020)
The purpose of this study is to investigate the effects of the COVID-19 pandemic on economic policy uncertainty in the US and the UK. The impact of the increase in COVID-19 cases and deaths in the country and the increase in the number of cases and deaths outside the country may vary. To examine this, the study employs the bootstrap ARDL cointegration approach from March 8, 2020 to May 24, 2020. According to the bootstrap ARDL results, a long-run equilibrium relationship is confirmed for five out of the ten models. The long-term coefficients obtained from the ARDL models suggest that an increase in COVID-19 cases and deaths outside of the UK and the US has a significant effect on economic policy uncertainty. The US is more affected by the increase in the number of COVID-19 cases. The UK, on the other hand, is more negatively affected by the increase in the number of COVID-19 deaths outside the country than the increase in the number of cases. Moreover, another significant finding from the study demonstrates that COVID-19 is a factor of great uncertainty for both countries in the short-term.
Keywords: Economic Policy Uncertainty; COVID-19; Bootstrap ARDL; Lockdown